The Speech Act Of Promising Among Saudi Female Efl Students: A Case Study At Jouf University - Abdo, Halemeh Naim Mustafa Buny (2023)
The current study investigated the ability of Saudi EFL students in the southern region of Saudi Arabia to produce and recognise utterances related to the speech acts of making promises. The qualitative study was conducted at Jouf University. To achieve the objectives set in the study, 20 hypothetical situations adapted from Beebe et al.’s (1990) DCT were selected. The 20 situations expressed the speech acts of promising and imitated real-life situations in Saudi Arabia; These situations were collected orally from 20 female Saudi students through semi-structured interviews (hereafter SSI) conducted with them. In addition, seven questions of the SSI were proposed to enhance and enrich the findings. The focus was placed on identifying the various ways of promising and identifying students’ problems when producing a promise and overcoming these problems in communication. Meanwhile, four focus group discussions (hereafter FGD) were held with the 16 participating female Saudi students, with four students in each group. The FGD sessions were conducted orally and were audio-recorded to identify the functions of the speech act of promising in communication. It also focused on the impact of Islamic culture on the production of the speech act of promising in communication. The study’s population for both the SSI and the FGD were chosen at random from the English Department at Jouf University in Tabarjal’s 3rd and 4th year- 5th, 6th, 7th, and 8th levels. The collected data were then transcribed using the NVivo software-12 version and analysed using thematic analysis. The study focused on the various responses to each question provided by each respondent. The speech acts were underlined in a variety of ways and functions. xvi One of them accurately pertains to the influence of Islamic culture on promising. The findings indicated that Saudi EFL students faced significant difficulties when it comes to producing and recognising the speech act of promising. Specifically, while 37% of students demonstrated the ability to recognise the speech act of promising, the overwhelming majority of students (63%) did not. Additionally, the findings showed that students frequently made unconditional promises rather than conditional promises, refusing promises, or delaying promises. In summary, the analysis revealed that Saudis issue pledges in various ways for various reasons. Also, it revealed that Saudis issue pledges for a variety of functions. Mainly, nine functions were identified when students opt for promising. Indeed, the current study made a contribution to linguistics by focusing on examining speech acts in general and the speech acts of promising in particular by focusing on the impact of Islamic culture on the production of the speech act of promising in communication. This is accomplished by highlighting the prominent ways and functions of the speech act of promising.